An integrated inventory model involving discrete setup cost reduction, variable safety factor, selling price dependent demand, and investment - Dey, Bikash Koli; Sarkar, Biswajit; Sarkar, Mitali; Pareek, Sarla (R.A.I.R.O. Recherche opérationnelle, 2019)
This paper develops a sustainable integrated inventory model for maximizing profit with a controllable lead time, discrete setup cost reduction, and consideration of environmental issues. Contrary to the available literature, this paper considers a discrete setup cost for the vendor, thus making the integrated model sustainable. The customer’s demand is assumed to be selling-price dependent to increase the number of sales, and the lead time demand follows a Poisson distribution. The integrated model is used to optimized the total shipment number, volume of shipments, safety factor, investments, selling-price, and probability of moving between the “in-control” to “out-of-control” states. An algorithm is developed to obtain the numerical results. Numerical examples and sensitivity analyses are given to illustrate the model.